Biorevitalization of the skin with skin boosters: Concepts, variables, and limitations. (8th December 2020) - Arora, Gulhima; Arora, Sandeep; Sadoughifar, Roxanna; Batra, Neha
Abstract: Aging leads to diminished capacity in the functionality of all the skin layers, which in turn leads to a structurally weak and esthetically unappealing skin which is dull, dehydrated, and inelastic. Skin boosters can be defined as biological materials or bio‐actives that help or encourage the skin to increase or improve its function. Boosters have been used in treating skin structural changes associated with aging as well as other factors such as corticosteroid‐induced skin atrophy. Restoring the loss in skin nourishment and vital components is the concept involved in biorevitalization of the skin. The authors aim to present an update and a short review of skin boosters in this commentary.